PVA and PVP nanofibers combined with Helichrysum italicum oil preserve skin cell interactions, elasticity and proliferation - Diletta Serra; Giuseppe Garroni; Sara Cruciani; Donatella Coradduzza; Aleksei Pashchenko; Evzen Amler; Giorgio Pintore; Pietro Parisse; Rosanna Satta; Fernanda Martini; Mauro Tognon; Antonio Brunetti; et al. (Scientific Reports)
Abstract Development of electrospun nanofibers with suitable properties to promote wound healing is an advantage in developing non-invasive skin treatments. We showed the potential application of Polyvinyl acetate (PVA) and Polyvinylpyrrolidone (PVP) combined with Helichrysum italicum oil (HO) in wound healing. During this process, Tight junctions (TJs) play a crucial role in maintaining skin integrity. TJs are intercellular junctions composed of a variety of transmembrane proteins, including Occludin (OCLN), observed also in migrating epithelial cells. Changes in OCLN expression affect epidermal permeability, indicating an active role in the healing process. Within this context, we studied the OCLN expression during healing after scratch assay on Keratinocytes (HaCaT), by a confocal microscopic analysis. In addition, we evaluated the effect of treatment after scratch on cell elasticity by Atomic Force Microscopy (AFM) analysis. All results show a positive trend in cell proliferation and viability on HaCaT treated with functionalized nanofibers. These results were confirmed by the expression of genes involved in the early stages of the regenerative process. Understanding the cell mechanisms involved in skin changes during repair process would allow future application of nanomaterials combined with HO in vivo.